Analysis of Route Selection Using the Analytical Hierarchy Process (AHP) in Mahakam Ulu Regency - Yulfadli, Zony; Adani, Sakila Herfiana Silmy; Nafis, Mochamad Abdillah (JSE Journal of Science and Engineering, 2025)
Roads are essential infrastructure for improving the economy of the community and regional development. Good road infrastructure certainly impacts the progress of an area. As the region develops and the complexity of the district government's tasks increases, which affects the increase in vehicle traffic, new road access is needed to facilitate the mobility of officials. The Analytical Hierarchy Process (AHP) method is one of the methods used for decision-making in project feasibility studies. In this study, there are four criteria used, namely 1. Distance 2. Efficiency, and; 3. Spatial Planning Integration and aesthetics. Each of these three criteria is broken down into two sub-criteria. Questionnaires were distributed to two respondents selected proportionally, consisting of one person from the Public Works Department of Mahakam Ulu Regency and one person from the Planning Consultant of PT. TEMA KARYA MANDIRI KSO. The questionnaire results were analyzed using the Analytical Hierarchy Process (AHP) method to assess four alternative road sections to be selected. Based on the AHP analysis of the main entrance road planning in the office area of Mahakam Ulu Regency, alternative location 1 was chosen with an AHP score of 0.473, which is higher than the other three alternatives. Therefore, alternative location 1 is recommended to proceed to the next study stage (Detail Engineering Design).